Elite in Sub-national Politics: Structure and Continuation in Post-authoritarian East Java, Indonesia - Aminuddin, M. Faishal; Ramadlan, M. Fajar Shodiq (Politika: Jurnal Ilmu Politik, 2022)
Study on political elites in sub-national politics in post-1998 Indonesia did not pay much attention to identify the shifting or continuation of structural change in the post-New Order authoritarianism. From a case study in East Java, this article shows the change and continuation of political elite structure. Democratization does not necessarily produce significant changes that shift the position and privilege of the old political elites. Their organizational power might have declined, but their control over patron-client relationship remains strong. This is also finds that the political changes were, institutionally, not strong enough to cause the significant damage to the patron-client relationship developed during the New Order era. The democratization pressure has only caused the partial diversification of elites’ political affiliation while the inter-intra elite power relations model has not changed much. This explanation provides a new contribution to the understandings on the dynamics and changes in the structure of political elites in sub-national politics in the era of democratization in Indonesia.